THE DEVELOPMENT OF NEXT-GENERATION BOILER FUELS: AN ANALYSIS OF GLOBAL AND NATIONAL CHEMICAL RESEARCH (Scientific journal of the Fergana State University, 2026)
This research analyzes modern scientific achievements in the field of producing boiler fuel from polymer waste. The article examines the chemical mechanisms of the pyrolysis process, catalytic systems, and technological parameters. The study results showed that 60-85% of plastic waste can be converted into liquid fuel during the pyrolysis process. The highest efficiency is achieved when the fast pyrolysis process is carried out at a temperature of 450-600°C. The article compares and analyzes the differences, achievements, and shortcomings in the scientific works of global and local scientists.